The Heritage of Karl Marx in the 21st Century: What are we Speaking About? - Chepurenko, Alexander (ZHURNAL SOTSIOLOGII I SOTSIALNOY ANTROPOLOGII (The Journal of Sociology and Social Anthropology), 2018)
The article introduces the new possibilities for the analysis of sociological views of Marx basing on the publication of his manuscripts, excerpts and epistolary heritage provided by the full academic edition of collected works of Karl Marx and Frederick Engels in the original languages (Marx-Engels-Gesamtausgabe, MEGA). It is shown that the manuscripts and original versions of “Capital” contain a number of ideas important for interpretation of sociological views of Marx (a commodity as the own result of the capital; private property as just a legal shell of the bourgeois economic relations; the logic and the stages of technological development on the basis of capital, etc.) which only fragmentary were reflected in the “Capital” itself. After the release of volume 1 (1867) Marx made several attempts to complete the “Сapital”, his preliminary versions of the books 2 and 3 show that he was evident of the core theoretical problems of the concluding parts of the book (such as the analysis of the reproduction of the total capital of the society and the explanation of the average rate of profit on the basis of the labour theory of value), but he never managed to solve them successfully. In the last period of his life Marx sparingly informed even his closest friends on the state and prospects of his work; many important ideas were not understood by them, including Engels who contributed to the formation of the orthodox “materialist understanding of history”. After Marx’s death, partly due to the complexity and difficulty of his theory, partly because of incompleteness of the drafts of the final parts of the “Capital” the Engels’ version of his ideas played an important role, influencing the largely popular interpretations of Marx’s theory. On their base, both the Historical Materialism and its criticism were formed. To enable an adequate perception of the heritage of Marx in the 21th century, the integration into the scientific discourse of those materials which became public only in the last decades is needed.